A study on Malaysian money market interest rates (with references of bankers acceptances and negotiable instruments of deposits) / Aisah Mat Tan - Mat Tan, Aisah (1997)
Money market is a significant part of a nation's financial system in which banks and other participants trade hundreds of million of dollars. It also can be defined as a wholesale market for low risk and highly liquid short term loans. This study was conducted to examine the relationship between money market interest rates (90 days of BA rate and 3 month NID rate) with other related factor ( 3 month interbank rate, inflation rate and exchange rate), as many investors feel that money market instruments as close substitutes changes in the money market interest rates are highly correlated . The investigation began with a review of the related empirical studies. This was followed by an overview of BAs and NIDs, in order to provide some knowledge and better understanding under this study. The empirical portion of this study employed a simple linear regression , multiple regression and trend analysis to examine the relationship between dependent variable (BA rate and NID rate) and independent variables (interbank rate, inflation rate and exchange rate ). The result of this study shows that both of the instruments rates have strong relationship with 3-month interbank rate and inflation rate but only a small portion of exchange rate that effect the 90 days of BA rate and 3 month of NID rate.